Prehospital Sinus Node Dysfunction and Asystole in a Previously Healthy Patient with COVID-19. (4th May 2022) - Powell, Megan; Ward, Brad; Dickson, Robert; Patrick, Casey
Abstract: We report a case of a previously healthy 47-year-old female with syncope due to multiple episodes of nodal dysfunction and asystole. During these brief episodes, she was hypoxic in the mid-80's as a result of COVID-19 pneumonia. The patient was admitted and treated for viral pneumonia and found to have normal electrocardiograms (ECG's), normal troponin levels and a normal echocardiogram during her hospital stay. As she recovered from COVID-19, no further episodes of bradycardia or bradyarrhythmia were noted. This case highlights a growing body of evidence that arrhythmias, specifically bradycardia, should be anticipated by prehospital providers as a potential cardiac complication of SARS-CoV-2 infection.